Revolutionary War on Wednesday - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Using their magic tree house, Jack and Annie travel back to the time of the American Revolution and help General George Washington during his famous crossing of the Delaware River.
"A Stepping stone book."
RL: 2.2.
006-009.
320
Accelerated Reader AR
Keywords: Washington, George, -- 1732-1799 -- Juvenile fiction; Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Tree houses -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Fantasy fiction; Historical fiction